2010
DOI: 10.1016/j.jmps.2009.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic fragmentation of ceramics, signature of defects and scaling of fragment sizes

Abstract: a b s t r a c tDefects play a critical role in the dynamic fragmentation process of structural ceramics. Cracks initiate at seemingly random locations, propagate and coalesce to form fragments. The process is accompanied by stress release waves, whose influence is difficult to account for without numerical analysis. In this paper, we use a finite-element program with a cohesive fracture capability, to relate a defect distribution contained in a material with the resulting number of fragments. We show how the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
57
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(63 citation statements)
references
References 23 publications
(21 reference statements)
6
57
0
Order By: Relevance
“…Recently, using expanding ring numerical tests, Levy and Molinari [10] generalized these expressions to heterogenous materials:…”
Section: Evolution Of the Average Fragment Size With Strain Ratementioning
confidence: 99%
See 3 more Smart Citations
“…Recently, using expanding ring numerical tests, Levy and Molinari [10] generalized these expressions to heterogenous materials:…”
Section: Evolution Of the Average Fragment Size With Strain Ratementioning
confidence: 99%
“…Therefore, similarly as the fragment size s ch , which is inverse proportional to the number of fragments, f 1 is a decreasing function of the left tail's slope of the cohesive strength distribution. Empirical arguments have shown that f 1 is comprised between 1 and √ 2 [10]. The second function f 2 is a decreasing function of the ratio between σ c,aver − σ c,min and σ c,aver , and is comprised between 0 and 1.…”
Section: Evolution Of the Average Fragment Size With Strain Ratementioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the small-scale 2D-MD simulations were also used by Sator and his collaborators (Sator et al, 2008, Sator andHietala, 2010) to investigate generic behaviors and damage evolution in the instantaneous point fragmentation of the LJ brittle solid colliding with a wall. In addition to MD, examples of computational techniques utilized recently in the dynamic fracture and fragmentation investigations include particle models (Baker and Warner, 2012;Kumar and Ghosh, 2015), discrete element models (Wittel et al, 2008;Iturrioz et al, 2009;Timar et al, 2010Timar et al, , 2012Paluszny et al, 2014), finite element methods (Levy and Molinari, 2010;Ugrcic, 2013), and meshfree methods (Wu et al, 2014;Li et al, 2012Li et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%